EVALUATION DES METAUX TRACES, PESTICIDES ET PLASTIFIANTS DANS LES PRODUITS MARAICHERS (GOMBO, CORETE POTAGERE, EPINARD ET AUBERGINE) DANS LAVALLEE DU NIEKI, SUD-EST DE LA COTE D’IVOIRE - Nantarie, Toure; Patrice, Kouadio Koffi; Emile, Yoboue Kouadio; Albert, Yao-Kouame (European Scientific Journal, ESJ, 2015)
A grade assessment study of metal trace metals (Cu, Zn, Cd and Pb), pesticides and plasticizers in market garden crops (Abelmoschus sp, Corchoruus tridens, Basela alba, Solanum aethiopicum) was performed in Niéki Valley in South-East of Côte d'Ivoire. This study found that trace metals found in the leaves and fruits grown on the different sampling sites are copper (Cu), Zinc (Zn), cadmium (Cd) and Lead (Pb). The Cu was accumulated in the leaves and the fruits. The Cu was accumulated in both the leaves and the fruits. The Cu concentrations in different plants far exceeded thelevels recommendedby the FAO (1 mg.kg-1). The Pb concentrations in different plants were between 106 and 109mg.kg- 1on all sites, far exceeding the thresholds set by the FAO (0.1 mg.kg-1of fresh material). Analyses of various plants showed that most elements are found pesticide family Pyrethroids (Bifenthrin, Deltamethrin and cyhalothrin) and a plasticizerof the phthalate family (1,2Benzenedicarboxylicacid, bis (2- ethylhexyl) ester). Doses of Bifenthrin determined in plants exceeded the acceptable daily intake (ADI) or (0.015 mg.kg-1), except in the case of Abelmoschus sp where these levels remain below the acceptable daily intake.